Minds, objects, and persons – narratives of perpetrators of violent crime - Dias, Angelo Ridge (My University, 2017)
Although research on violence has gained momentum over the last 3 decades, very little work on situational factors involved in violent enactments has been undertaken in South Africa. As a means to address this limitation, the aim of this project was to better understand the phenomenology of violence. Embedded in a psychosocial approach, the study subjected data collected through three staggered semi-structured interviews with nineteen incarcerated perpetrators of violent crime to a twostage secondary data analysis using Interpretative Phenomenological Analysis. The first phase, aimed to provide a broad general phenomenological reading of these fifty-seven interviews. Thereafter, a more strategic and theory driven analysis was performed, building on the broader reports of the phenomenology of violence and the perceived situational factors. The evidence suggests that neoliberal policies and ideology may have a significant role in production of violent crime in the South African context, informing not only the behavioural repertoire of its constituency, but, also coming to shape the way in which perpetrators make meaning of their lifeworld and perpetration of violent crime. The analysis also found that impairments in mentalization appeared to play a role as a situational determinant in violent enactments, and interestingly it appeared to be influenced by a number of other relevant situational factors (e.g. the presence and use of illicit substances, peer and social presence and pressure, indicators of a possible threat to their wellbeing, the presence of gangsters, the presence of indicators of conspicuous consumption, as well as, indicators of the presence of moral disengagement). As such, this study provides strong support for further research aimed at understanding the ways in which violence comes to be produced by the structural processes of neoliberalism, it’s influence on the subjectivity of individuals in neoliberalized contexts, and its arguably corrosive effect on marginalized communities by way of its divestment, as well as, its arguably negative sociocultural impact. The project’s overall contribution to psychosocial approaches to violence lies in its demonstration of the value of bridging theories that span work on moral disengagement, conspicuous consumption, neoliberalism, mentalization theory, phenomenology, and violence.
Submitted in accordance with the partial requirements for the degree of Masters in Community Based Counselling Psychology in the Faculty of Humanities at the University of Witwatersrand, 2017
Keywords: Violent crimes--South Africa; Criminals--South Africa--Interviews; Violence--South Africa--Psychological aspects